International Monetary Fund Annual Report 1966. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1966)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1966. The report highlights that the year 1965 was characterized by substantial, although somewhat uneven, growth in the world economy. For the first time in many years, the rise in industrial output in the United States and Canada was markedly higher than in the other industrial countries, where, in the first half of the year, economic progress was generally rather slow. However, after midyear, economic activity accelerated both in the United States and in the European area.